The HLA-Cw12 Allele Is an Important Susceptibility Allele for Psoriasis and Is Associated with Resistant Psoriasis in the Turkish Population - Nahide Onsun; Serpil Pirmit; Dilek Ozkaya; Şirin Çelik; Aylin Rezvani; F. Pelin Cengiz; Cigdem Kekik (The Scientific World Journal)
Background. Psoriasis is a multifactorial immune-mediated inflammatory disease triggered by both genetic and environmental factors. The strong association between psoriasis and HLA-C⁎06 allele has been demonstrated in various races. The HLA-C⁎12 allele is closely related to the HLA-C⁎06 family of alleles and shares identical sequences. To the best of our knowledge, there is no information about the relationship between HLA-C⁎12 and psoriasis in the Turkish population. The present study aims to determine this relationship. Methods. This case control study involved 150 patients with plaque-type psoriasis and 145 age- and gender-matched healthy individuals. Severity of psoriasis was measured using the PASI scores of all patients and joint involvement was investigated with CASPAR criteria. HLA-C alleles were determined with a Tepnel-Lifecodes system. Results. HLA-C⁎06, HLA-C⁎12, and HLA-C⁎04 alleles were most commonly observed in psoriasis patients. HLA-C⁎06 and HLA-C⁎12 were significantly more frequent in the psoriasis group. HLA-C⁎06 was 4.11 times more common in psoriasis patients. An increase in PASI (Psoriasis Area Severity Index) scores was compatible with HLA-C⁎12 positivity. A need for systemic treatment was highly noticeable in patients with the HLA-C⁎12 allele. Conclusions. HLA-C⁎12 was found as the second most frequent allele with psoriasis in Turkish population and was associated with severe psoriasis. Our study is limited as we could not investigate other potentially related alleles other than HLA-C alleles and risk factors increasing severity of psoriasis.